The Headmen Divison Performance Of Religious Affairs Office (Kua) Singaran Pati Sub-District Of Bengkulu City(Study at the KUA office, Singaran Pati Sub-District, Bengkulu City) - Eka Dewi Larasati; Asnawati Asnawati; Antonio Imanda (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2021)
The purpose of this study is to determine the Performance of the Headman division of Religious Affairs Office (KUA) Singaran Pati Sub-District, Bengkulu City (Study at the KUA Office Singaran Pati Sub-District, Bengkulu City). The research method uses a descriptive method with a qualitative approach. As an analytical tool in conducting this research, the researcher used Wibowo's theory of performance management which consists of seven indicators, namely goals, standards, feedback, tools or means, competencies, opportunities and motives. Informants consist of key informants, totaling nine people. Data were collected using interview techniques, observation and documentation. The results of this study indicate that the purpose of the headman division is to reduce the level of underage marriage by socializing Law No. 16 of 2019 to the general public. The standard from the division is to work according to the SOP and TUPOKSI applicable at the KUA, Singaran Pati sub-district, Bengkulu City. Feedback from the division in reducing the level of child marriage is very good based on the policy of the Ministry of Religion and the input given by the head of the KUA. The tools or facilities for the division in reducing the level of child marriage, seen from other facilities, are not yet adequate. The competencies possessed by the division are in accordance with the standards set by Law No. 16 of 2019 concerning the age limit for marriage. The opportunities from the division in reducing the level of child marriages are to provide opportunities for employees to promote brochures on the dangers of marrying under the age of 19. The motive of the division in reducing the level of age marriage, is the existence of a decree from the Ministry of Religion to disseminate information on the prevention of child marriage based on Law No. in terms of performance, it is quite good, but the researcher found findings that have an impact on the performance of KUA Singaran Pati Sub-District headman, where there are still minors who are still doing underage marriages, this is due to promiscuity and many are pregnant out of wedlock so that the parties of KUA Singaran Pati Sub-District Bengkulu City must marry off the couple.